Accelerated implementation of remote reporting during the COVID-19 pandemic. Issue 6 (June 2021) - Callaway, M.; Greenhalgh, R.; Harden, S.; Elford, J.; Drinkwater, K.; Vanburen, T.; Ramsden, W.
Abstract : AIM: To assess, via a survey of UK radiological departments, if the COVID-19 pandemic led to a change in radiological reporting undertaken in a home environment with appropriate IT support. MATERIALS AND METHODS: All imaging departments in the UK were contacted and asked about the provision of home reporting and IT support before and after the first wave of the pandemic. RESULTS: One hundred and thirty-seven of the 217 departments contacted replied, producing a response rate of 61%. There was a 147% increase in the provision of remote access viewing and reporting platforms during the pandemic. Although 578 consultants had access to a viewing platform pre-pandemic, this had increased to 1, 431 during the course of the first wave. CONCLUSION: This survey represents work undertaken by UK NHS Trusts in co-ordinating and providing increased home-reporting facilities to UK radiologists during the first wave of this global pandemic. The impact of these facilities has been shown to allow more than just the provision of reporting of both elective and emergency imaging and provides additional flexibility in how UK radiologists can help support and provide services. This is a good start, but there are potential problems that now need to be overcome. Highlights: 147% increase in remote access reporting achieved during the first wave of the Covid-19 pandemic. Remote working allows flexibility other than reporting; such as MDT meetings. A different way of working for radiologists was rolled out during the Covid-19 pandemic.